Non-medical opioid use and sources of opioids among pregnant and non-pregnant reproductive-aged women() - Kozhimannil, Katy B. (Drug Alcohol Depend, 2017)
BACKGROUND: The morbidity and mortality burden of the US opioid epidemic falls heavily on reproductive-age women. Information on the patterns of and sources for non-medical use of prescription opioids among reproductive age women, including pregnant women, will inform public health and prevention efforts to mitigate the effects of the opioid epidemic. This study characterized non-medical use of prescription opioids among reproductive-age U.S. women, with a focus on pregnancy status. METHODS: We used nationally-representative data from the National Survey of Drug Use and Health (2005–2014) to examine non-medical use (NMU) of prescription opioids in the past 30 days among females ages 18–44 (N=154,179), distinguishing pregnant women (N=8,069). We used multivariable logistic regression to describe reported sources of opioids, including opioids obtained from a doctor, friend or relative, dealer, or other source. RESULTS: Nearly 1% of pregnant women and 2.3% of non-pregnant reproductive-age women reported opioid NMU in the past 30 days. Forty-six percent of pregnant women identified a doctor as their source compared with 27.6% of non-pregnant women reporting NMU. Pregnant women reported a friend or relative as their source of opioids less frequently than non-pregnant women (53.8% versus 75.0%), and some pregnant and non-pregnant women acquired opioids from a dealer (14.6% and 10.6%). CONCLUSION: Opioid NMU among reproductive-age women is a complex public health challenge affecting a vulnerable population. Pregnant women were more likely than non-pregnant women to list a doctor as their source of opioids for NMU, suggesting the need for targeted policies to address physician prescribing during pregnancy.